2022
DOI: 10.18343/jipi.27.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Preprocessing Factors Affected Free Fatty Acid Content in Crude Palm Oil Quality

Abstract: The quality of CPO (Crude Palm Oil) is determined by the Free Fatty Acid (FFA) with the standard value below 5%. High FFA in CPO will cause further difficulties due to low refining rate and quality like rancidness and odor. The objective of this research was to determine the factors that affect the FFA content in CPO. This research was conducted from January until April 2021. Fruit samples were collected from BKLE and PNRE East Kotawaringin and analyzed to Analytical Laboratory PT BGA. The FFA value was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Mele and Giuffré (2018) suggested that environmental, agronomic, and genetic factors such as climate, tree age, and species could affect the oil content of fruits. This finding was supported by Edyson et al (2022) and Zaouay et al (2020) who found that fruit maturity, variety, handling, and pest infestations significantly influenced the fruit's oil content. Therefore, it was initially expected that the results would be insignificant since both RT and RS belong to the same genetic type, which is red colour Rambutan Nephelium lappaceum (Anak Sekolah/ Clone R191).…”
Section: Oil Contentmentioning
confidence: 57%
“…Mele and Giuffré (2018) suggested that environmental, agronomic, and genetic factors such as climate, tree age, and species could affect the oil content of fruits. This finding was supported by Edyson et al (2022) and Zaouay et al (2020) who found that fruit maturity, variety, handling, and pest infestations significantly influenced the fruit's oil content. Therefore, it was initially expected that the results would be insignificant since both RT and RS belong to the same genetic type, which is red colour Rambutan Nephelium lappaceum (Anak Sekolah/ Clone R191).…”
Section: Oil Contentmentioning
confidence: 57%
“…At ambient temperature, the extracted crude palm oil contains carotenes, which are subsequently discarded. The hydrolysis of fatty acids during the extraction process is the primary mechanism responsible for the production of free fatty acids in palm oil [12][13][14][15][16][17]. In addition, free fatty acids occur naturally in crude palm oil and can be generated through various processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have claimed that, apart from the endogenous lipases, exogenous lipase, which is produced from microbial sources, may also play a role in FFA accumulation in oil palm fruits [10,11]. Previous studies have reported that pre-and post-harvesting factors, such as pest attacks, the maturity of fruits, handling, and delayed delivery to the mill, are the main causes of increased FFAs in both FFB and LF [10,12].…”
Section: Introductionmentioning
confidence: 99%